Bacteriocin - producing lactic acid bactera isolated from budu, fermented chilli and tempoyak made of Malaysian durian musang king. / Sharifah Khairundalila Sayed Milam - Sayed Milam, Sharifah Khairundalila (2015)
Recently, there has been a concern on the natural preservatives in preserving foods. For this reason, many studies have been done in order to investigate and identify the microorganisms that can be used as biopreservatives, which are the lactic acid bacteria (LAB). LAB can produce bacteriocin that able to inhibit the growth of pathogenic organisms. However, this study was done due to lacking of studies on the LAB isolated from Malaysian traditional fermented foods such as budu, fermented chilli and tempoyak made of Malaysian Durian Musang King. Hence, the objective of this study is to screen the potential of the bacteriocin producing LAB from the trad\tional fermented food and also to study the effect of proteolytic enzymes towards them. The antimicrobial activity of the bacteriocin was tested against the selected indicator organisms which are Staphylococcus aureus (ATCC 43300), Bacillus cereus (ATCC 14579), Escherichia coli (ATCC 25922), Salmonella typhimurium (ATCC 13311) and Listeria monocytogenes (ATCC 7644). Four LAB isolated from tempoyak made of Malaysian Durian Musang King (Lactobacillus plantarum 1, Leuconostoc mesenteroides ssp dextranicum 2, Pediococcus pentosaceus, and Lactobacillus plantarum 1), two from fermented chilli (Lactobacillus plantarum 1, and Lactobacillus fructivoran) and one from budu (Weissella cibaria) were re-cultured from stock cultures stored at -20°C and -40 °C, and the antimicrobial activity of the bacteriocin produced by the isolated LAB were tested against the selected indicator organisms by using disc diffusion method. The activity of bacteriocin is represented as the inhibition zone around the disc. Among the entire isolated LAB, LAB T6 (Leuconostoc mesenteroides ssp dextranicum 2) and LAB C3 (Lactobacillus fructivoran) were the best in showing inhibition activity against indicator organisms upon elimination of organic acid and hydrogen peroxide. The activity of bacteriocin towards the indicator organisms were inactivated after treated with proteolytic enzymes, the Proteinase K and trypsin. This finding indicates that, the bacteriocin produced by the isolated LAB does have the ability to inhibit pathogenic organisms and are safe for human consumption.